2020
DOI: 10.1126/science.abb9847
|View full text |Cite
|
Sign up to set email alerts
|

Stem-like CD8 T cells mediate response of adoptive cell immunotherapy against human cancer

Abstract: Adoptive T cell therapy (ACT) using ex vivo–expanded autologous tumor-infiltrating lymphocytes (TILs) can mediate complete regression of certain human cancers. The impact of TIL phenotypes on clinical success of TIL-ACT is currently unclear. Using high-dimensional analysis of human ACT products, we identified a memory-progenitor CD39-negative stem-like phenotype (CD39−CD69−) associated with complete cancer regression and TIL persistence and a terminally differentiated CD39-positive state (CD39+CD69+) associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
320
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(329 citation statements)
references
References 66 publications
9
320
0
Order By: Relevance
“… 188 An increased understanding might facilitate in vitro strategies to increase the percentage of tumour-reactive stem-like TILs, for example, which have been shown to be capable of self-renewal, expansion, persistence and a superior anti-tumour response in patients with melanoma. 189 …”
Section: Cancer–immune System Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“… 188 An increased understanding might facilitate in vitro strategies to increase the percentage of tumour-reactive stem-like TILs, for example, which have been shown to be capable of self-renewal, expansion, persistence and a superior anti-tumour response in patients with melanoma. 189 …”
Section: Cancer–immune System Interactionsmentioning
confidence: 99%
“… 198 200 The enrichment of this subpopulation during TIL expansion could therefore enhance the efficacy of ACT therapies. 189 , 201 …”
Section: Cancer–immune System Interactionsmentioning
confidence: 99%
“…demonstrated that CD39 and CD69 expression can be used to bifurcate patient response to cell therapy and that some CD39 -TIL from these patients are neoantigen recognizing stem-like T cells, which are known to potentiate powerful antitumor responses 43 . Thus, it is likely that the reduced CD39 and overt expression of IL-2R and ICOS on T cells post CpG treatment potentiate T cell function, metabolism, and persistence in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CD39 marks effector T cells that have an exhausted phenotype in patients with infectious disease and cancer and have reduced survival after activation in older individuals 28,29 42 . In patients with metastatic melanoma, Krishna et al demonstrated that CD39 and CD69 expression can be used to bifurcate patient response to cell therapy and that some CD39 - TIL from these patients are neoantigen recognizing stem-like T cells, which are known to potentiate powerful antitumor responses 43 . Thus, it is likely that the reduced CD39 and overt expression of IL-2Rα and ICOS on T cells post CpG treatment potentiate T cell function, metabolism, and persistence in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic fitness and T cell function are closely related and ways to target the T cell metabolism were recently reviewed. 103 For example, transient glucose restriction 104 and using stemlike CD8 cells 105 were shown to improve the efficacy of T cells in ACT approaches.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%